Development of solid agents of the diphenyl ether herbicide degrading bacterium Bacillus sp. Za based on a mixed organic fertilizer carrier - Zhao, Guoqiang; Tian, Yanning; Yu, Houyu; Li, Jintao; Mao, Dongmei; Faisal, Rayan Mazin; Huang, Xing (Frontiers in Microbiology, 2022)
The long-term and widespread use of diphenyl ether herbicides has caused serious soil residue problems and threatens the agricultural ecological environment. The development of biodegrading agents using high-efficiency degrading strains as pesticide residue remediation materials has been widely recognized. In this study, the strain Bacillus sp. Za was used to prepare solid agents for the remediation of diphenyl ether herbicides-contaminated soil. The ratio of organic fertilizer was 1:3 (pig manure: cow dung), the inoculum amount of Za was 10%, the application amount of solid agents was 7%, and the application mode was mixed application, all of which were the most suitable conditions for solid agents. After the solid agents were stored for 120 days, the amount of Za remained above 108 CFU/g. The degradation rates of the solid agents for lactofen, bifenox, fluoroglycofen and fomesafen in soil reached 87.40%, 82.40%, 78.20%, and 65.20%, respectively, on the 7th day. The application of solid agents alleviated the toxic effect of lactofen residues on maize seedlings. a confocal laser scanning microscope (CLSM) was used to observe the colonization of Za-gfp on the surface of maize roots treated in the solid agents, and Za-gfp mainly colonized the elongation zone and the mature area of maize root tips, and the colonization time exceeded 21 days. High-throughput sequencing analysis of soil community structural changes in CK, J (solid agents), Y (lactofen) and JY (solid agents+lactofen) groups showed that the addition of solid agents could restore the bacterial community structure in the rhizosphere soil of maize seedlings. The development of solid agents can facilitate the remediation of soil contaminated with diphenyl ether herbicide residues and improve the technical level of the microbial degradation of pesticide residues.